APPLICATION OF THE BANDONGAN METHOD AT ISLAMIC BOARDING SCHOOL - Syamsudin, Arif (SYAHADAT: Journal of Islamic Studies, 2024)
This study aims to examine the activities in the salafiyah boarding school and its role as an Islamic civilization in Indonesia. The thing that is in the spotlight of many people is how the existence of salafiyah boarding school activities for Islamic civilization in society in particular. In some cases, this type of salafiyah boarding school is able to be a solution to creating people with noble character because the culture in traditional boarding schools is able to provide uniqueness to an education. The purpose of this study is to find out and analyze (1) the profile of the Islamic boarding school (2) the Islamic education system (3) the Islamic education program (4) the implementation of Islamic education for Islamic civilization (5) the evaluation system. This study uses a case study method using a qualitative approach. Data collection uses observation, interview, documentation, and triangulation techniques. The researcher is the key instrument in this study. Analysis of research data is carried out in the form of data reduction, data display, and verification. Based on the results of the study, it was found that this salafiyah boarding school still maintains its existence in implementing activities in it. Because, the boarding school is part of Islamic civilization in Indonesia. This Salafiyah Islamic boarding school also still maintains a traditional education system, making this Islamic boarding school very unique in its implementation.